Anastomotic False Aneurysm of the Aorta: Closure With a "Sandwiched" Coil. (June 2015) - Barbetta, Iacopo; Giovannacci, Luca; Canevascini, Reto; van den Berg, Jos C.
Purpose: To describe the treatment of a noninfected saccular anastomotic false aneurysm (AFA) of the abdominal aorta with the use of a single "sandwiched" coil.Case Report: A 65-year-old man presented with a saccular AFA of the distal anastomosis exactly at the level of the aortic bifurcation 1 month after open abdominal aortic aneurysm repair. Endograft exclusion was not attempted because an aortouni-iliac configuration would have sacrificed a patent iliac axis. Coil embolization was the preferred strategy. Use of 3-dimensional rotational angiography and 3-dimensional roadmap was necessary to cannulate the neck of the AFA. Complete thrombosis and shrinkage of the sac was achieved by "sandwich coiling" of the neck after deployment of a single pushable hydrogel-coated coil. Imaging at 9 months postprocedure showed no sign of the aneurysm sac.Conclusion: This novel technique can be used for selected saccular AFAs with a narrow neck. In such cases, sandwich coiling may avoid sacrifice of a patent iliac axis.